Development of a novel PCV2 and PCV3 vaccine using virus-like vesicles incorporating Venezuelan equine encephalomyelitis virus-containing vesicular stomatitis virus glycoprotein - Wang, Ying; Su, Min; Huang, Yongshuang; Ren, Jianle; Niu, Sheng; Zhao, Yujun; Yan, Fang; Yan, Yi; Tian, Wen-xia (Frontiers in Veterinary Science, 2024)
Porcine circovirus disease (PCV) causes substantial economic losses in the pig industry, primarily from porcine circovirus type 2 (PCV2) and porcine circovirus type 3 (PCV3). Novel vaccines are necessary to prevent and control PCV infections. PCV coat proteins are crucial for eliciting immunogenic proteins that induce the production of antibodies and immune responses. A vaccine platform utilizing Semliki Forest virus RNA replicons expressing vesicular stomatitis virus glycoprotein (VSV-G), was recently developed. This platform generates virus-like vesicles ( VLVs) containing VSV-G exclusively, excluding other viral structural proteins. In our study, we developed a novel virus-like vesicle vaccine by constructing recombinant virus-like vesicles (rVLVs) that also express EGFP. These rVLVs were created using the RNA replicon of Venezuelan equine encephalomyelitis (VEEV) and New Jersey serotype VSV-G. The rVLVs underwent characterization and safety evaluation in vitro. Subsequently, rVLVs expressing PCV2d-Cap and PCV3-Cap proteins were constructed. Immunization of C57 mice with these rVLVs led to a significant increase in anti-porcine circovirus type 2 and type 3 capsid protein antibodies in mouse serum. Additionally, a cellular immune response was induced, as evidenced by high production of IFN-γ and IL-4 cytokines. Overall, this study demonstrates the feasibility of developing a novel porcine circovirus disease vaccine based on rVLVs.